Indelible shadows : film and the Holocaust - Insdorf, Annette (Cambridge University Press, 2003)
The third edition of Indelible Shadows includes five new chapters. It addresses the treatment of rescuers, as in 'Schindler's List'; the controversial use of humor, as in 'Life is Beautiful'; the distorted image of survivors, and the growing genre of documentaries that return to the scene of the crime or rescue.